Relationships between the microstructure and fracture toughness of microalloyed (API 5L X65) steels - Tas, Z; Sönmez, N (CARL HANSER VERLAG, 2005)
The present article is intended to examine the relationships between the microstructure and the fracture mechanical properties. It uses the J integral concept for a characterization of the properties of fracture mechanics. The microalloyed steels of the X65/API-5L type were used for this purpose. Some of the individual microstructures were characterized qualitatively, others quantitatively, by means of a light microscope (LM) and a scanning electron microscope (SEM). The examinations of the size and distribution of the non-metallic inclusions and precipitates were made by means of a SEM and an LM, in some cases. Tensile tests and notch bend impact tests were performed to determine the mechanical properties. The properties of fracture mechanics were examined on three-point bending test samples at a room temperature. The multi-sample method was employed to determine the crack growth resistance curve.
Keywords: Metallurgy & Metallurgical Engineering